The Concept of Hubbul Watani (Patriotism) in the Light of Seerah Tayyiba ﷺ: A Research Study in the Context of State Loyalty and Muslim Ummah - Dr. Nisar Mehmood (Journal of Religion and Society, 2026)
This study seeks to understand the issue of Hubbul Watani (patriotism) in the context of the Seerah (biography) of Prophet Muhammad ﷺ, and its compatibility with state loyalty and the global Muslim Ummah. This research reflects on the growing conflict between the modern nation-state model, which seeks exclusive political loyalty, and the concept of Ummah in Islam, which emphasises brotherhood among Muslims across the world. Using primary sources of Islam, especially the Quran, Hadith and the Constitution of Medina (Mithaq-e-Madina), this study shows that Islam acknowledges patriotism as a natural human feeling. The Prophet ﷺ loved Makkah and Madinah and founded a model city-state which combined local citizenship duties with global Muslim brotherhood. The research finds that Seerah offers a middle ground: it embraces jā’iz (permissible) patriotism based on service, justice, and loyalty to one's country, but condemns nationalism when it leads to racial superiority, discrimination or defiance of Shariah. The research also examines how this might be applied in Pakistan today. It explains that the Ideology of Pakistan offers a balanced perspective where love for the homeland is not opposed to love for the Ummah. The findings suggest that Islamic patriotism is expressed in civic responsibilities, national progress, justice and, efforts to promote the well-being of state and world Muslim populations. The study finds that Islam neither embraces cosmopolitanism without roots nor chauvinistic nationalism. Rather, it provides a moderate, moral framework of patriotism that unites state and Ummah. This balanced perspective offers a pragmatic framework for Muslim nations grappling with issues of globalisation, identity politics and state-building. Keywords: Hubbul Watani, Patriotism in Islam, Seerah of Prophet Muhammad ﷺ, Constitution of Medina, State Loyalty, Muslim Ummah, Islamic Nationalism, Pakistan Ideology, Civic Responsibility, Moderate Patriotism